1996
DOI: 10.1074/jbc.271.42.25830
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Active-site Residues in the Hydroxynitrile Lyase from Manihot esculenta by Site-directed Mutagenesis

Abstract: The hydroxynitrile lyase from cassava (Manihot esculenta Crantz) (EC 4.1.2.37) catalyzes the decomposition of the achiral ␣-hydroxynitrile acetone cyanohydrin into HCN and acetone during cyanogenesis of damaged plants. This enzyme can also be used for stereoselective synthesis of a wide array of (S)-cyanohydrins by addition of HCN to aldehydes or ketones. Optically active cyanohydrins are interesting intermediates for the synthesis of ␣-hydroxy acids, ␣-hydroxy ketones, or ␤-ethanolamines, all of which are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 22 publications
3
57
3
Order By: Relevance
“…As shown in Figure 1A, purified cassava HNL had a subunit molecular mass of 28.5 kD, similar to that reported by Hughes et al (1994) and Wajant and Pfizenmaier (1996). The native enzyme, however, had a molecular mass of 50.1 kD, suggesting that it was a dimer (Fig.…”
Section: Purification and Characterization Of Cassava Hnlsupporting
confidence: 69%
See 3 more Smart Citations
“…As shown in Figure 1A, purified cassava HNL had a subunit molecular mass of 28.5 kD, similar to that reported by Hughes et al (1994) and Wajant and Pfizenmaier (1996). The native enzyme, however, had a molecular mass of 50.1 kD, suggesting that it was a dimer (Fig.…”
Section: Purification and Characterization Of Cassava Hnlsupporting
confidence: 69%
“…1B). These results are in contrast to those of Hughes et al (1994), Chueskul andChulavatnatol (1996), and Wajant and Pfizenmaier (1996). Hughes et al (1994) reported that the native molecular mass of HNL was a 92-kD homotrimer, whereas the latter two groups reported that the native enzyme was a tetramer of 102 to 110 kD, respectively.…”
Section: Purification and Characterization Of Cassava Hnlcontrasting
confidence: 56%
See 2 more Smart Citations
“…The second hydrolysis mechanism is typically referred to as the general base mechanism. This typically begins with substrate deprotonation (Sun et al, 2014;Wajant & Pfizenmaier, 1996;Zuegg et al, 1999). In the case of ZHD, this enzyme-product structure provides the final state of catalysis.…”
Section: Resultsmentioning
confidence: 99%